100 Inequality Problems
100 Inequality Problems
100 Inequality Problems
b 1b + c 1c
r
b+c 1 1
≥ b
· c
b+c b c
b c b+c
=⇒ (2b) (2c) ≥ (b + c) .
We obtain two analogous inequalities and multiplying all of them yields
the desired result.
Equality holds iff a = b = c.
QED.
1
Join us at: https://t.me/Maths_Olympiad_2024
Problem 2
ln(1+x)
The function f (x) = x is convex and decreasing. By Chebyshev and
Jensen, we have
X a2 ln(1 + bc) 1 X 2 X ln(1 + ab)
≥ a
bc 3 ab P
ab
1 X 2 3 ln 1 + 3
≥ a · P
ab
3
3 P 2
a
1 X 2 3 ln 1 + 3
≥ a · P
a2
3
3
4
= 3 ln
3
64
= ln .
27
Problem 3
2
√a
P
Let I = cyc a2 +1
. Then by using Holder’s Inequality, we obtain
! !3
X a2 + 1 X
2
I ≥ a
cyc
a cyc
( cyc a)3
P
2
=⇒ I ≥ P a2 +1 .
cyc a
Problem 4
8(cos2 A
2 − sin2 A 2 B 2 B
2 )(cos 2 − sin 2 )(cos 2
2 C
− sin2 C
2)
≤
sin2 A2 sin2 B2 sin2 C2
A B C
csc2 csc2 csc2 ,
2 2 2
Problem 5
We
Pn shall prove a more general result ∀ai ∈ R+ (i = 1, · · · , n(≥ 2)), if
2
i=1 ai = 1, then
n
X 1 n3
2
≥ ,
i=1
(1 + ai ai+1 ) (n + 1)2
where an+1 = a1 .
Using Cauchy-Schwarz Inequality, we obtain
n n
!2
X 1 1 X 1
2
≥
i=1
(1 + ai ai+1 ) n i=1
1 + ai ai+1
2
n2
1
≥ n
n
X
(1 + ai ai+1 )
i=1
n3
= !2
n
X
n+ ai ai+1
i=1
n3
≥ !2
n
1X 2
a + a2i+1
n+
2 i=1 i
n3
= .
(n + 1)2
Problem 6
Note that
X a(b + c)
cyc
b2 + bc + c2
X 4a(b + c)(bc + ca + ab)
=
cyc
4(b2 + bc + c2 )(bc + ca + ab)
X 4a(bc + ca + ab)
≥ .
cyc
(b + c)(a + b + c)2
or
X a (a + b + c)2
≥ .
cyc
b+c 2(bc + ca + ab)
Problem 7
Note that
a2 + b2 = a + b =⇒ a + b ≤ 2.
Therefore, Titu’s Lemma & AM-GM gives us
a b 1
+ +
2b + 1 2a + 1 2ab + 1
(a + b)2 1
≥ +
4ab + a + b 2ab + 1
2ab 1
≥ +
2ab + 1 2ab + 1
= 1.
Problem 8
a b kab a2 + ab + b2 kab √
+ + 2 = + − 1 ≥ 2 k − 1.
b a a + ab + b2 ab a2 + ab + b2
√ √ √
a k−1± k−2 k−3
Equality is obtained for = 2 .
b
QED.
Problem 9
a b c
√ +√ +√
7a2 + b2 + c2 a2 + 7b2 + c2 a2 + b2 + 7c2
= f (a2 ) + f (b2 ) + f (c2 )
2
a + b2 + c2
≤ 3f
3
= 1
by Jensen Inequality.
Equality holds iff a = b = c.
QED.
Problem 10
1 ax 1 ay 1 az
ax + by + cz = xyz · + · + ·
x yz y zx z xy
x x1 y y1 z z1
a a a
≥ xyz
yz zx xy
abcxyz
= 1 1 1
(yz) x (zx) y (xy) z
abcxyz
= 2
1 1 1 1 1 1
x 2y y 2z z 2y y 2x z 2y x 2z
abcxyz
≥ 2
x y z y z x
2y + 2z + 2x + 2x + 2y + 2z
4abcxyz
= 2
x2 y+xy 2 +y 2 z+yz 2 +z 2 x+zx2
xyz
4abcxyz
= 2
x2 y+xy 2 +y 2 z+yz 2 +z 2 x+zx2 +3xyz
xyz −3
4abcxyz
= 2
(x+y+z)(xy+yz+zx)
xyz −3
4abcxyz
= .
(x + y + z − 3)2
Problem 11
We have
1 1 1
√ +√ +√
2
2a + 1 2
2b + 1 2c2 + 1
9
≥√ √ √
2a + 1 + 2b2 + 1 + 2c2 + 1
2
3
≥q
2a2 +1+2b2 +1+2c2 +1
3
√
3 3
≥q
a+b+c 2
6 3 +3
√
= 3.
Problem 12
1 1 1
Let a, b & c ∈ R+ with a + b + c = 1. Show that
1 1 1
Since a, b, c > 0 and a + b + c = 1, we get
3
√
3
≤1
abc
thereby
abc ≥ 27,
and so the Weighted AM-GM shows
aa bb cc 1 1 1
+ + ≥ (aa ) a (bb ) b (cc ) c = abc ≥ 27,
a b c
which gives
Problem 13
a2 + b2 − c2 ≥ k(c − a)(c − b)
a2 + b2 − c2 ≥ k(c − a)(c − b)
a3 + b3
⇐⇒ a2 + b2 − ≥ k(c − a)(c − b)
c
⇐⇒ (c − a)a2 + (c − b)b2 ≥ kc(c − a)(c − b)
c3 − b3 c3 − a 3
⇐⇒ (c − a) · + (c − b) · ≥ kc(c − a)(c − b)
a b
⇐⇒ (c2 + cb + b2 )b + (c2 + ca + a2 )a ≥ kabc
⇐⇒ c2 (a + b) + c(a2 + b2 ) + a3 + b3 ≥ kabc
⇐⇒ c(a + b) + a2 + b2 + c2 ≥ kab
p p 2
⇐⇒ (a + b) a3 + b3 + a2 + b2 +
3 3
a3 + b3 ≥ kab.
p p 2 √ √
a3 + b3 + a2 + b2 +
3 3 3 3
(a + b) a3 + b3 ≥ (2 2 + 2 + 4)ab.
√ √
The equality occurs for a = b. Hence, the answer is indeed 2 3 2+2+ 3 4.
QED.
Problem 14
We have
b3 + c3 ≥ bc(b + c) ⇐⇒ (b + c)(b − c)2 ≥ 0.
Thus,
X bc X bc 3
≤ = .
cyc
b3 3
+ c + abc cyc
bc(a + b + c) a + b+c
Problem 15
x2 y2 z2
Let a = yz , b = zx , c = xy . Then the inequality we need to prove becomes
y 6 + z 6 ≥ yz(y 4 + z 4 ) ⇐⇒ (y 5 − z 5 )(y − z) ≥ 0.
Therefore,
Y Y
(y 6 + z 6 ) ≥ x2 y 2 z 2 (y 4 + z 4 )
cyc cyc
sY
= x2 y 2 z 2 (y 4 + z 4 )2
cyc
sY
= x2 y 2 z 2 (x4 + y 4 )(x4 + z 4 )
cyc
Y
≥ x2 y 2 z 2 (x4 + y 2 z 2 ). [By Cauchy-Schwarz]
cyc
Problem 16
We have
X a2 (a + b + c)(a2 + b2 + c2 )
≥
cyc
b+c 2(bc + ca + ab)
X X Y X X
⇐⇒ 2 bc a2 (a + b)(a + c) − b+c a a2 ≥ 0
cyc cyc cyc cyc cyc
X X
2
⇐⇒ 2abc a(a − b)(a − c) + abc a(b − c)
cyc cyc
X X
+4 b2 c2 (b − c)2 + bc(b − c)4 ≥ 0.
cyc cyc
Problem 17
Homogenization gives
!2 !3
X X
3 bc(b + c) ≥4 bc .
cyc cyc
Which simplifies to
X X
3 b2 c2 (b2 + c2 ) + 2 b3 c3 ≥ 24a2 b2 c2 .
cyc cyc
Problem 18
a2 + b2 + c2
1 8 a b c
+ ≥ + + .
ab + bc + ca 3 9 b+c c+a a+b
=⇒ (pq − 9r)(p2 + q) ≥ 0.
The last inequality is obvious by AM-GM.
Equality holds iff a = b = c.
QED.
Problem 19
Problem 20
Note that
Therefore, √
b3 + c2 1
≥√ .
b2 + c2 b+c
Thus, √
X a b3 + c3 X a
≥ √ .
cyc
b2 + c2 cyc
b+c
!2 √
X a (a + b + c)3 3(a + b + c) 3 3 abc 9
i.e. √ ≥ ≥ ≥ = .
cyc
b+c 2(bc + ca + ab) 2 2 2
Problem 21
Problem 22
Indeed, by Holder
!2 !3
X 1 X 8a + bc X 1
√ ≥ =1
cyc
8a + bc cyc
(a + 2)3 cyc
a+2
2x
which after substitution a = and similar gives
y+z
X
(x5 y − x3 y 3 + 4x4 yz − 2x3 y 2 z − 2x2 y 2 z 2 ) ≥ 0,
sym
Problem 23
a b
Let a, b & c ∈ R+ with a + b + c = b + c + ac . Prove that
1 1 1
+ + ≤ 1.
b2 + c2 + 1 c2 + a2 + 1 a2 + b2 + 1
By Cauchy-Schwarz,
(a + b + c)2 ≥ a2 + b2 + c2 + 6 ⇐⇒ ab + bc + ca ≥ 3.
a b c (a + b + c)2
a+b+c= + + ≥
b c a ab + bc + ca
=⇒ ab + bc + ca ≥ a + b + c
=⇒ (ab + bc + ca)2 ≥ (a + b + c)2 ≥ 3(ab + bc + ca)
=⇒ ab + bc + ca ≥ 3.
Equality holds iff a = b = c = 1.
QED.
Problem 24
4p2 − (q + 1)2 ≤ q − 1,
⇐⇒ 4p2 ≤ q 2 + 3q
!2 !2
X X X
⇐⇒ 4 a ≤ bc + 3 bc
cyc cyc cyc
!2
X X 3abc X
⇐⇒ 4abc a≤ bc + · bc
cyc cyc
a + b + c cyc
X X
⇐⇒ 2abc a2 ≤ b2 c2 (b + c).
cyc cyc
Problem 25
a3 + b3 + c3 ≥ 2(b2 c2 + c2 a2 + a2 b2 ).
x y z
Let a = , b = and c = . Thus, yz + zx + xy + xyz = 4 and we need
2 2 2
to prove that
x3 + y 3 + z 3 ≥ y 2 z 2 + z 2 x2 + x2 y 2 .
Now, from the condition and Cauchy-Schwarz,
X x (x + y + z)2
1= ≥ P 2 ,
cyc
x+2 (x + 2x)
cyc
which gives
yz + zx + xy
1≥ ,
x+y+z
(x3 + y 3 + z 3 )(yz + zx + xy)
⇐⇒ x3 + y 3 + x3 ≥
x+y+z
and it’s enough to prove that
Problem 26
(c − b)b(s − b) ≥ (c − b)c(s − c) ⇐⇒ (c − b) c2 − b2 − cs + bs ≥ 0
2
⇐⇒ (c − b) (c + b − s) ≥ 0.
Problem 27
a3 + b3 + c3 2r
≥4− .
abc R
A B C r
Use the identity sin2 + sin2 + sin2 = 1− , where r and R are
2 2 2 2R
in inradius and circumradius respectively.
r
A (s − b)(s − c)
Also, recall the identity sin 2 = and its cyclic counter-
bc
parts.
Now, a = (s − b) + (s − c). Therefore,
Problem 28
Note that
1 1
≥ 2 ⇐⇒ (b − c)4 ≥ 0.
2b + 5bc + 2c2
p
4 4
2(b + c ) + 7bc
1
≥ .
a+b+c
Problem 29
A B C
We can replace sin , sin & sin by x, y & z. Then we need to prove
2 2 2
that
2(yz + zx + xy) ≤ x + y + z.
Subject to the condition x2 + y 2 + z 2 + 2xyz = 1.
Note that
X x
1 ≥ yz + zx + xy + 2xyz ⇐⇒ 1 ≥ .
cyc
x+1
⇐⇒ x + y + z ≥ 2(yz + zx + xy).
Equality holds iff ∆ABC is equilateral.
QED.
Problem 30
By Cauchy Schwarz,
" #2 !
Xp X xz X
xz(2x + z) ≤ (2x + z)(x + z),
cyc cyc
x+z cyc
Problem 31
a = y + z, b = z + x & c = x + y.
bc
Claim:
P
cyc = 1.
(ra + rb )(ra + rc )
Proof: We have
X bc X (z + x)(x + y)
=
cyc
(ra + rb )(ra + rc ) (∆ + ∆
cyc x
∆ ∆
y )( x + z )
X x
=
cyc
x + y+z
= 1.
p + q + r ≥ 9,
Problem 32
a = y + z, b = z + x & c = x + y.
Claim: ra + rb ≥ 2hc .
Proof: This is
1 1 4
+ ≥ .
x y x+y
Which follows from Titu’s Lemma.
Hence, our desired inequality follows immediately.
Equality holds iff ∆ABC is equilateral.
QED.
Problem 33
Hence,
X 1
≤ 1.
cyc
a3 +2
Problem 34
b3 c3 a3 a+b+c
+ 2 + 2 ≥ .
b2 + bc + c2 c + ca + a2 a + ab + b2 3
Note that
2
a3 2a b (a + b)(a − b)
2 2
≥ − ⇐⇒ ≥ 0.
a + ab + b 3 3 3(a2 + ab + b2 )
Problem 35
Since
2
(b + c − a)2 (b + c)2 a2 + b2 + c2 − ab − ac
+ 1 = + ,
b2 + c 2 a2 + b2 + c2 (b2 + c2 ) (a2 + b2 + c2 )
we have
X (b + c − a)2
+3
cyc
b2 + c2
X a2 + b2 + c2 − ab − ac 2
" #
1 X
= 2 (b + c)2 +
a + b2 + c2 cyc cyc
b2 + c2
X a2 + b2 + c2 − ab − ac 2
2(bc + ca + ab) 1
=2+ + 2
a2 + b2 + c2 a + b2 + c2 cyc b2 + c2
2
2(bc + ca + ab) 3a2 + 3b2 + 3c2 − 2bc − 2ca − 2ab
≥2+ + 2
a2 + b2 + c2 2 (a2 + b2 + c2 )
2
9 bc + ca + ab
= +2 1− 2 .
2 a + b2 + c2
Problem 36
√
xb
Let a = √ , where x > 0. Thus, after squaring twice, we obtain
3
b
Equality holds iff x = 1 i.e. a = √ .
3
QED.
Problem 37
By Chebyshev, we have
3 2
6(a3 + b3 + c3 + d3 ) ≥ (a + b2 + c2 + d2 ).
2
1 2 1
(a + b2 + c2 + d2 ) ≥ .
2 8
Problem 38
7(cos A + cos B + cos C) ≤ 9 + 2(cos B cos C + cos C cos A + cos A cos B).
X X
⇐⇒ 9 + 2 cos B cos C ≥ 7 cos A.
cyc cyc
Problem 39
4r2 + 16Rr ≤ a2 + b2 + c2 .
bc + ca + ab = s2 + r2 + 4Rr.
Problem 40
R b c
≥ + .
r c b
Let la , lb & lc denote the angle bisectors and ha , hb & hc denote the
altitudes. Then, we have
Problem 41
Let f (x) = x1x , where x > 0. Then, f is concave in (0, 1). Thus, by
Jensen Inequality, we obtain
Hence,
Problem 42
r(R − 2r) X
2
+7 cos A ≤ 9 + 2(cos B cos C + cos C cos A + cos A cos B).
R cyc
We have
R+r
cos A + cos B + cos C =
R
and
s2 − 4R2 + r2
cos B cos C + cos C cos A + cos A cos B = .
4R2
Therefore, we need to prove that
s2 ≥ 16Rr − 5r2 .
Problem 43
Problem 44
√
r
3 r2 + 4Rr s
r2 s ≤ ≤ .
3 3
Problem 45
tan2 A
Q
8(tan A + tan B + tan C)3 8 tan3 A tan3 B tan3 C cyc
Q = Q ≤ .
27 cyc (tan B + tan C) 27 cyc (tan B + tan C) 27
tan2 A
Q
(1 − cos A)(1 − cos B)(1 − cos C) cyc
≥
cos A cos B cos C 27
Problem 46
Note that
abc
R2 ≥ .
a+b+c
Therefore, we need to prove that
abc(ma + mb + mc ) ≥ 2∆(a2 + b2 + c2 )
2∆(a + b + c)2
=⇒ abc(ma + mb + mc ) ≥ .
3
Where the last inequality follows from QM-AM.
Equality holds iff ∆ABC is equilateral.
QED.
Problem 47
Note that
a2 + b2
≤ (a2 − a + 1)(b2 − b + 1).
2
Also, we have
a2 + ab + b2 a2 + b2
≤ ⇐⇒ (a − b)2 ≥ 0.
3 2
Hence, Y Y
(b2 + bc + c2 ) ≤ (a2 − a + 1)2 ≤ 1
cyc cyc
Y
=⇒ (b2 + bc + c2 ) ≤ 1.
cyc
Problem 48
x
as the function f = is convex.
1+x
Let x2 = a, y 2 = b and z 2 = c and assume a + b + c = 1. Notice that by
applying AM-GM on the denominator, we obtain
X x2 X 2a X 2a 3
LHS = ≥ = ≥
cyc
y(x + y) + z(x + z) cyc
2a + 3b + 3c cyc
3 − a 4
x
as the function f (x) = is convex.
3−x
Therefore,
X x2 3 X x
≥ ≥ .
cyc
y(x + y) + z(x + z) 4 cyc
(x + y) + (x + z)
Problem 49
because
x1 = x2 = ...x9 = 1, x10 = 49
and
f (1, 1, ..., 1, 49) = 492 + 9 = 2410.
Let b − a ≥ 2 then
because
an + (10 − n)(a + 1) = 58
=⇒ n = 10a − 48 → n = 2, a = 5.
Then,
f (5, 5, 6, 6, ..., 6) = 50 + 8 × 36 = 338.
Problem 50
But
b+c √
a≥ ≥ bc.
2
Thus, √
(a + b + c)(a + 2 bc) ≥ 9bc > 6bc.
Also, we have
1
f , x, x ≥ 5 ⇐⇒ (x − 1)2 (2x4 + 4x3 − 4x2 − x + 2) ≥ 0.
x2
√ √ 1 √ √
f (a, b, c) ≥ f (a, bc, bc) ≥ f , bc, bc ≥ 5.
bc
Problem 51
(x − y)(xy(x + y) − 2)
≥ 0.
xy
Using our Lemma, we obtain
a 2x x 2x x
b a+c b+c
+2 ≥ + .
b a b+c a+c
a x x x x x
b c x a+c b+a c+b
=⇒ + + ≥ + + .
b c a b+c c+a a+b
Equality holds iff a = b = c.
QED.
Problem 52
Problem 53
x2 + xy 2 + xyz 2 ≥ 4xyz − 4.
We have
Problem 54
Homogenize to get
X
ab(a + b + c)2 − 2a2 b2 ≥ 7abc(a + b + c).
cyc
Expanding gives
X X
a3 b+ ≥ a2 bc.
cyc cyc
Problem 55
Problem 56
3r2 r 2
⇐⇒ + q−2− ≥ 0.
4 2
Equality holds iff r = 0, p = 3, & q = 2 or a = 2, b = 1, c = 0 and cyclic
permutations.
QED.
Problem 57
We have
X s2 + r2 − 4R2
cos B cos C = .
cyc
4R2
X r
cos A = 1 + .
cyc
R
X s2 + r2 + 4Rr
sin B sin C = .
cyc
4R2
s2 ≤ 4R2 + 6Rr − r2 .
Which is clearly true since it’s weaker than Gerretsen’s Inequality, i.e.
s2 ≤ 4R2 + 4Rr + 3r2 . Indeed,
Problem 58
a b c a b c 1
+ + ≥ + + ≥ .
4 − bc 4 − ac 4 − ab 4 4 4 2
If a, b, c are all strictly positive, then the inequality abc < 2bc is strict,
so a + b + c > 2 and the desired inequality is also strict.
We have
yz + zx + xy + xyz = 4
X 1
⇐⇒ =1
cyc
x+2
X 1
⇐⇒ bc
=1
cyc a
+2
X a
⇐⇒ = 1.
cyc
2a + bc
Problem 59
We have
Y A r
sin = .
cyc
2 4R
Y s2 − r2 − 4Rr − 4R2
cos A = .
cyc
4R2
s2 ≤ 4R2 + 5Rr + r2 .
Which is clearly true since it’s weaker than Gerretsen’s Inequality, i.e.
s2 ≤ 4R2 + 4Rr + 3r2 . Indeed,
Problem 60
b2 c2 + c2 a2 + a2 b2 ≥ 3abc.
√ √ √
Let a = yz, b = xz and c = xy, where x, y and z are positives.
Then, the condition gives
yz + zx + xy + xyz = 4
X 1
⇐⇒ =1
cyc
x+2
X 1
⇐⇒ bc
=1
cyc a
+2
X a
⇐⇒ = 1.
cyc
2a + bc
⇐⇒ b2 c2 + c2 a2 + a2 b2 ≥ 3abc.
Equality holds iff a = b = c = 1.
QED.
Problem 61
We have
sin A sin B sin C Y A r
=2 sin = .
sin A + sin B + sin C cyc
2 R
Y s2 − r2 − 4Rr − 4R2
cos A = .
cyc
4R2
X 6R2 + r2 + 4Rr − s2
cos2 A = .
cyc
2R2
s2 ≤ 4R2 + 5Rr + r2 .
Thus,
3s2 R + 2s2 r ≤ 12R3 + 2r3 + 23R2 r + 13Rr2 .
So, it remains to prove that
⇐⇒ 2r ≤ R.
Which is just Euler’s Inequality.
Equality holds iff ∆ABC is equilateral.
QED.
Problem 62
Problem 63
a4 b4 c4 1
+ 4 + 4 ≤ .
4a4 4
+b +c 4 4
a + 4b + c 4 a + b4 + 4c4 2
4a4 + b4 + c4
= 2a4 + (a4 + b4 ) + (a4 + c4 )
≥ 2a2 (a2 + b2 + c2 ).
Therefore,
X a4 X a2 1
≤ = .
cyc
4a4 + b4 + c4 cyc
2a2 (a2 + b2 + c2 ) 2
Problem 64
Using the identity, (a + b + c)2 = (−a + b + c)2 + 4a(b + c), the condition
bc + ca + ab = 1 and Cauchy Schwarz, we obtain
a+b+c
p
= [(−a + b + c)2 + 4a(b + c)][bc + a(b + c)]
√
≥ | − a + b + c| bc + 2a(b + c)
√
= (−a + b + c)(a + bc) + a(a + b + c).
1−a −a + b + c
⇐⇒ √ ≥ .
a + bc a+b+c
Therefore,
√
X 1 + a bc
√
cyc a + bc
√
X (1 − a2 ) + a(a + a bc)
= √
cyc a + bc
X X 1−a
= a+ (1 + a) · √
cyc cyc a + bc
X 1 X
≥ a+ (1 + a)(−a + b + c)
cyc
a + b + c cyc
X 1
≥ a+ · [(a + b + c) − (a + b + c)2 + 4(bc + ca + ab)]
cyc
a + b+c
4
= 1+ .
a+b+c
Problem 65
√
r r r
a2 + 5bc b2 + 5ca c2 + 5ab
+ + ≤ 3 2.
a2 + 2bc b2 + 2ca c2 + 2ab
Note that
a2 + 5bc 2a2 + 5b2 + 5c2
2
≤ ⇐⇒ 0 ≤ (b − c)2 .
a + 2bc 2(a2 + b2 + c2 )
cyc
a2 + 2bc
s
X 2a2 + 5b2 + 5c2
≤
cyc
2(a2 + b2 + c2 )
s
36(a2 + b2 + c2 )
≤
2(a2 + b2 + c2 )
√
= 3 2.
Problem 66
We have
12R4 + 4r4 + 16Rr3 + 27R2 r2 + 12R3 r − (3R2 + 4r2 )s2
LHS−RHS = .
2R2 (6R2 − p2 + r2 + 4Rr)
or
12R4 + 12R3 r + 27R2 r2 + 16Rr3 + 4r4
s2 ≤ .
3R2 + 4r2
Indeed, we see that
Problem 67
45(a2 + b2 + c2 )
2 2 2 1 1 1
(a + b + c ) 2 + + ≥
b + c2 c2 + a2 a2 + b2 8(a2 + b2 + c2 + 1)
2 2 2
a b c 21(a2 + b2 + c2 ) − 24
⇐⇒ 2 + + ≥ .
b + c2 c2 + a 2 a 2 + b2 8(a2 + b2 + c2 + 1)
a2 b2 c2 (a2 + b2 + c2 )2
+ + ≥ .
b2 + c2 c2 + a2 a2 + b2 b2 c2 + c2 a2 + a2 b2
Therefore, we need to prove that
(a2 + b2 + c2 )2 21(a2 + b2 + c2 ) − 24
≥
b2 c2 + c2 a2 + a2 b2 8(a2 + b2 + c2 + 1)
which is equivalent to
Problem 68
Problem 69
The angle bisectors of ∆ABC meet the sides BC, CA, AB at the
points D, E, F respectively. Prove that
EF 2 + F D2 + DE 2 ≥ 9r2 .
2abc∆
[DEF ] = ∆ − ([AEF ] + [BF D] + [CDE]) = .
(b + c)(c + a)(a + b)
Now,
√ using the formulas abc = 4R∆, ∆ = rs and Mitrinovic’s Inequality,
(3 3R ≥ 2s) we obtain
√
27 2 2 3 3 2
[DEF ] ≥ · 8Rr s ≥ r .
64s3 4
Hence,
√
EF 2 + F D2 + DE 2 ≥ 4 3[DEF ] ≥ 9r2 .
Equality holds iff ∆ABC is equilateral.
QED.
Problem 70
Problem 71
Problem 72
If (an )∞
n=1 denote an arithmetic progression with common dif-
ference d. If both a1 and d are positive, prove that
a2p a2q a2r
+ + ≥ 3.
aq+r ar+p ap+q
Problem 73
Let a = tan A, b = tan B & c = tan C. Then the given condition implies
that A + B + C = π. Thus, we need to prove that
X
sec B sec C ≥ 4 + sec A sec B sec C
cyc
X
⇐⇒ cos A − 4 cos A cos B cos C ≥ 1.
cyc
Note that
Y s2 − r2 − 4Rr − 4R2
cos A = .
cyc
4R2
X R+r
cos A = .
cyc
R
s2 ≤ 4R2 + 5Rr + r2 .
Which is clearly true since it’s weaker than Gerretsen’s Inequality, i.e.
s2 ≤ 4R2 + 4Rr + 3r2 . Indeed,
Problem 74
a4 + b3 c + c3 b ≥ abc(a + b + c).
2a
Let t = , then
b+c
a3 b2 + c2 4a3 (b + c)2
+ ≥ + .
bc a (b + c)2 2a
4a3 (b + c)2
2
+ ≥ a + b + c,
(b + c) 2a
or
2
t3 + ≥ t + 2,
t
(t2 + 2t + 2)(t − 1)2
⇐⇒ ≥ 0.
t
Which is clearly true.
Equality holds iff 2a = b + c.
QED.
Problem 75
which is equivalent to
X
x3 + y 3 + z 3 + 3xyz ≥ yz(y + z).
cyc
Problem 76
Problem 77
Now, by AM-GM
v
u P a 3
Xa u 2 b +3
4
u cyc
2 + 3 + abc(a + b + c) ≥ 4 t abc(a + b + c)
cyc
b 3
or
X X X
x3 + 3xyz − yz(y + z) + x(x − y)2 ≥ 0.
cyc cyc cyc
Problem 78
Since
1 1 1
2
+ 2
≥
(a + 1) (b + 1) ab + 1
and
abc abc2
≥ ,
4 (c + 1)2
it suffices to show that
1 abc2 + 1
+ ≥ 1,
ab + 1 (c + 1)2
(abc − 1)2
⇐⇒ ≥ 0.
(ab + 1)(c + 1)2
Which is obviously true.
Equality holds iff a = b = c = 1.
QED.
Problem 79
R (b + c)(c + a)(a + b)
+1≥ .
2r 4abc
R s2 + 2Rr + r2
+1≥ .
2r 8Rr
Therefore, we need to prove that
s2 ≤ 4R2 + 6Rr − r2 .
Which is clearly true since it’s weaker than Gerretsen’s Inequality, i.e.
s2 ≤ 4R2 + 4Rr + 3r2 . Indeed,
Problem 80
p2 3(p − 1)
≥
p+3 4
⇐⇒ (p − 3)2 ≥ 0.
Equality holds iff a = b = c = 1.
QED.
Problem 81
Note that
bc + ca + ab ≤ a2 + b2 + c2 .
Therefore, we need to prove that
a2 + b2 + c2
(a − 1)2 + (b − 1)2 + (c − 1)2 ≥ −3
2
X X
⇐⇒ a2 + 12 ≥ a.
cyc cyc
that
p2
+ 12 ≥ 4p
3
⇐⇒ (p − 6)2 ≥ 0.
Equality holds iff a = b = c = 2.
QED.
Problem 82
p2
Let p = a + b + c, q = bc + ca + ab, x = p2 − 2q = a2 + b2 + c2 & y = .
q
Now, use Titu’s Lemma to obtain
X b+c 4(a + b + c)2
p ≥P p .
cyc 2(b2 + c2 ) 2 2
cyc (b + c) 2(b + c )
Thus,
X b+c 2p2
p ≥p .
cyc 2(b2 + c2 ) 2x(x + q)
Therefore, we need to prove that
2
2p2 2p4
3x 9 9 3x
p + ≥ ⇐⇒ ≥ −
2x(x + q) 2q 2 x(x + q) 2 2q
⇐⇒ 8p4 q 2 ≥ 9(p2 − 2q)(p2 − q)(p2 − 5q)2
⇐⇒ 117p6 + 855p2 q 3 ≥ 9p8 + 505p4 q 2 + 450q 4
855 450
⇐⇒ 117y + ≥ 9y 2 + 505 + 2
y y
⇐⇒ (y − 3)(150 − 235y + 90y 2 − 9y 3 ) ≥ 0.
′
Let f (y) = 150 − 235y + 90y 2 − 9y 3 then, it’s clear that f (y) > 0. Thus,
f is increasing. And since y ≥ 3, we have
Problem 83
This is equivalent to
X a3 (b30 c5 + c30 b5 )
≥ 3.
cyc
b15 c3 + c15 b3
cyc
b15 c3 + c15 b3
X a(b25 + c25 )
=
b12 + c12
cyc
√
X a b13 c13 (b12 + c12 )
≥
cyc
b12 + c12
X√
= b11 c11
cyc
≥ 3.
Problem 84
a2 − bc b2 − cd c2 − da d2 − ab
+ + + ≥ 0.
2a + b + c 2b + c + d 2c + d + a 2d + a + b
We have
a2 − bc (a + b)2
= − b.
2a + b + c 2a + b + c
Now, use Titus’s Lemma to obtain
X a2 − bc
cyc
2a + b + c
X (a + b)2 X
= − a
cyc
2a + b + c cyc
X 4(a + b + c + d)2
≥ − (a + b + c + d)
cyc
4(a + b + c + d)
= 0.
Problem 85
Problem 86
Problem 87
We have
Problem 88
(cos A + cos B + cos C)2 ≥ sin B sin C + sin C sin A + sin A sin B.
We have X r
cos A = 1 + .
cyc
R
X s2 + r2 + 4Rr
sin B sin C = .
cyc
4R2
Problem 89
We have
X a
≤1
cyc
4 − b
X 3a
⇐⇒ ≤1
cyc
4(a + b + c) − 3b
X a 1
⇐⇒ ≤
cyc
4a + b + 4c 3
X a2 + ab + ac a+b+c
⇐⇒ ≤
cyc
4a + b + 4c 3
X a2 + ab + ac a
a+b+c a+b+c
⇐⇒ − ≤ −
cyc
4a + b + 4c 4 3 4
X ab a+b+c
⇐⇒ ≤ .
cyc
4a + b + 4c 9
a+b+c
= .
9
1
Equality holds iff a = b = c = .
3
QED.
Problem 90
a2 + b2 + c2 a2 + b2 + 2c2
≥
ab + bc + ca ab + bc + ca + c2
a2 + b2 + 2c2
=
(b + c)(c + a)
Therefore,
!2
a2 + b2 + 2c2 (a2 − b2 )2
=1+
4(b2 + c2 )(c2 + a2 )
p
2 (b2 + c2 )(c2 + a2 )
(a2 − b2 )2
≥1+
4(b2 + ab)(ab + a2 )
(a2 − b2 )2
≥1+
(a + b)4
2(a + b2 )
2
=
(a + b)2
p
a2 + b2 + 2c2 2(a2 + b2 )
⇐⇒ p ≥
2 (b2 + c2 )(c2 + a2 ) a+b
p
a2 + b2 + 2c2 8(b2 + c2 )(c2 + a2 )(a2 + b2 )
⇐⇒ ≥
(b + c)(c + a) (b + c)(c + a)(a + b)
p
a2 + b2 + c2 8(b2 + c2 )(c2 + a2 )(a2 + b2 )
=⇒ ≥ .
bc + ca + ab (b + c)(c + a)(a + b)
Problem 91
P
Use AM-GM to obtain cyc a ≥ 3 and
X X X X
a2 = (a − 1)2 + 2 a−3≥ a.
cyc cyc cyc cyc
So,
X X1 X X
p a2 + q =p a2 + q ab
cyc cyc
a cyc cyc
X X
= (p − q) a2 + q (a2 + ab)
cyc cyc
X 1 X
2
= (p − q) a + q (a + b)2
cyc
2 cyc
2
P
X 1 4( cyc a)
≥ (p − q) a + q( )
cyc
2 3
X X
= (p − q) a + 2q a
cyc cyc
X
= (p + q) a.
cyc
Problem 92
(a − b)(b − c)(a − c) ≤ 2.
x + y ≤ 2.
So, we have
2
x+y
(a − b)(b − c)(a − c) = xy(x + y) ≤ (x + y) ≤ 2.
2
Problem 93
b2 c2 + c2 a2 + a2 b2
R2 ≥ .
3(a2 + b2 + c2 )
Note that
ma ≥ ha
√
2b2 + 2c2 − a2 bc
⇐⇒ ≥
2 2R
⇐⇒ R2 (2b2 + 2c2 − a2 ) ≥ b2 c2 .
Problem 94
61 3 1
⇐⇒ p + 9r − 4pq + (pq − 9r) ≥ 0.
81 81
Which follows from Schur’s Inequality and AM-GM.
Equality holds iff a = b = c
QED.
Problem 95
Let bc = x, ca = y & ab = z.
Thus, by Holder’s Inequality
r
X bc
cyc
8a + bc
s √
X x x
= √ √
cyc
x x + 8 yz
v
u !2
√ P √ √ √
u Pq
x x
√ √ x x x x + 8 yz
u
u
u cyc x x+8 yz
cyc
=u P √ √ √
x x x x + 8 yz
t
cyc
v
u (x + y + z)3
≥ u
tP √ √ √ .
x x x x + 8 yz
cyc
X X
⇐⇒ 27 y 2 z 2 (y 2 + z 2 )+54 y3 z3 ≥
cyc cyc
X X
3
10xyz x +30xyz yz(y + z) + 114x2 y 2 z 2 .
cyc cyc
Problem 96
4 − a2 4 − b2 4 − c2
+ + ≤ 3.
4 − ab 4 − bc 4 − ca
The first sum is nonnegative by AM-GM. Let’s work with the second
one. After homogenization, it is equivalent to
X X
4(a3 b + b3 c + c3 a) + (a3 c + b3 a + c3 b) ≥ 4 b2 c2 + abc a.
cyc cyc
Problem 97
Note that
1 b+c
≤ ⇐⇒ 0 ≤ bc(b − c)2 .
2(b2 + 3bc + c2 )
p
(4b + c)(4c + b)
Therefore,
X 1 X b+c 3(a + b + c)
p ≤ 2 2
≤ .
cyc (4b + c)(4c + b) cyc
2(b + 3bc + c ) 5(ab + ac + bc)
Problem 98
Problem 99
Problem 100
So
4
LHS − RHS = −3a4 + 12a3 − 16a2 + 8a −
3
4
= −3a4 + 6a3 − 2a2 + 6a3 − 12a2 + 4a − 2a2 + 4a −
3
1
= − (3a2 − 6a + 2)2 ≤ 0.
3
In ∆ABC
• Sides: BC = a, CA = b, AB = c
• Semiperimeter: s
• Ravi Substitution: a = y + z, b = z + x, c = x + y
• Area: ∆
• Circumradius: R
• Inradius: r
• Exradii: ra , rb , rc
• Medians: ma , mb , mc
• Angle Bisectors: la , lb , lc
• Altitudes: ha , hb , hc
• Symmedians: sa , sb , sc
• abc = 4Rrs
• bc + ca + ab = s2 + r2 + 4Rr
1 2
•
P
cyc =
cos A + cos B cos C cos A + cos B + cos C − 1
s2 + r2 − 4R2
•
P
cyc cos B cos C =
4R2
r
• cos A + cos B + cos C = 1 +
R
6R2 + r2 + 4Rr − s2
• cos2 A + cos2 B + cos2 C =
2R2
s2 − r2 − 4Rr − 4R2
• cos A cos B cos C =
4R2
s
• sin A + sin B + sin C =
R
rs
• sin A sin B sin C =
2R2
s2 + r2 + 4Rr
•
P
cyc sin B sin C =
4R2